A Review on Dual-Lens Fluorescence Microscopy for Three-Dimensional Imaging - Li, Xiaoyan; Han, Yubing; Liu, Wenjie; Kuang, Cuifang; Liu, Xu; Hao, Xiang (Frontiers in Physics, 2020)
Three-dimensional (3D) imaging using dual-lens fluorescence microscopies is popular in observing fluorescently-labelled biological samples, such as mammalian/model animal cells, tissues, and embryos. Specifically, dual-lens super-resolution fluorescence microscopy methods using two opposing objective lenses allow significantly higher axial resolution and better signal to noise ratio compared with traditional single-lens counterparts and thus distinguish more details in 3D images of fine intracellular structures. For 3D imaging of thick tissues and entire embryos, dual-lens light-sheet fluorescence microscopy methods using two objective lenses either orthogonal or non-orthogonal to achieve selective plane illumination can meet the requirements, and thus can be used to observe embryo development and structures of interest in thick tissues. This Review summarizes both dual-lens fluorescence microscopy methods, including their principles, configurations and 3D imaging applications, providing a guideline for biological laboratories with different 3D imaging needs.